Strategi Pemasaran Online UMKM Makanan (Studi Kasus di Kecamatan Cibinong) - Setiawan, Teguh Febrianto; Suharjo, Budi; Syamsun, Muhammad (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2018)
Online marketing is a method of marketing using online (OL) and electronic media. This study aims to, (1) Assess the effectiveness of (OL) marketing in increasing corporate income, (2) Describe products that have OL marketing potential, ( 3) Identify influential factors in developing OL marketing strategies, and (4) Providing recommendations for alternative OL marketing strategies to be applied in MSMEs. This research was conducted on 10 MSMEs in Cibinong Sub-district, Bogor Regency, West Java Province, from April to August 2018. The method of analysis consists of descriptive analysis, content analysis, Strength, Weaknesses, Opportunity, and Threat (SWOT) analysis and Analytic Hierarchy Process (AHP). Based on the analysis of research data it is known that OL marketing successfully increases income for respondents by 10% to 32%. The results of content analysis found that the respondents' MSMEs already knew the importance of attracting product visualization by displaying descriptions and images that could invite consumers to buy, but not fully optimized yet through the Google Review Knowledge Panel facility. Based on the SWOT analysis, strategies were obtained: (a) Business Development with support of available Human Resource (HR) & Marketing Media Support, (b) Business Development System (OL), (c) Business Scale Up by Utilizing Capital, (d) Skill Improvement and OL System Knowledge, (e) Increased Business Capital and Product Promotion Display in order increasing turnover,( f) Business Development through Product Variants, Taste and Promotions (g) Increasing business capacity and services (Delivery), (h) Increasing cooperation in OL product promotion, (i) Increasing innovation and new product variants. The alternative method of OL marketing of food MSMEs in Cibinong Sub district chosen based on AHP respectively is Grab-food media. The second priority is to use social media (Facebook, Instagram, Youtube etc.). The third priority is to use Google SEO media. The fourth priority is to use a website and the fifth priority is direct contact.